1994
DOI: 10.1038/clpt.1994.13
|View full text |Cite
|
Sign up to set email alerts
|

Topical glaucoma medications and cardiovascular risk in the elderly

Abstract: Major cardiovascular side effects did not occur at an increased rate among patients using topical beta-blockers or other glaucoma medications compared with control subjects. This population-based study places findings from case reports and small clinical trials in a broader context to help with clinical assessment of the risks and benefits of glaucoma therapy in the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…It is comforting that a recent review disclosed that major cardiovascular side effects did not occur at an increased rate in a population‐based study of elderly patients using topical β blockers or other glaucoma medications, compared to normal subjects 35 . These observations are in line with the belief that individuals with underlying pulmonary and/or cardiac abnormalities are likely to be those most susceptible to adverse effects from systemic β blockade.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…It is comforting that a recent review disclosed that major cardiovascular side effects did not occur at an increased rate in a population‐based study of elderly patients using topical β blockers or other glaucoma medications, compared to normal subjects 35 . These observations are in line with the belief that individuals with underlying pulmonary and/or cardiac abnormalities are likely to be those most susceptible to adverse effects from systemic β blockade.…”
Section: Discussionmentioning
confidence: 71%
“…These can include either physiologic β blocker effects (e.g., bradycardia) or complications known to accompany use of this drug class. Thus, it should be no great surprise that topical β blockade can lead to bradyarrhythmias, syncope, daytime and/or nocturnal hypotension, congestive heart failure, reduced exercise tolerance, and/or lipid abnormalities 12,28–37 …”
Section: Cardiac Effectsmentioning
confidence: 99%
“…Interestingly when beta blocker was used topically for treatment of glaucoma, it additionally caused CHF 71 . In an epidemiological study, no association between use of topical beta blocker and CHF was found 72 .…”
Section: Beta -Adrenoceptor Antagonist Andmentioning
confidence: 95%
“…Recognition and management of systemic sequelae, patient intolerance to adverse events, and the impact of these factors on compliance with therapy and quality of life have previously been discussed and reviewed in the literature. [61][62][63] Several new glaucoma agents with demonstrated efficacy in reducing IOP have been shown to have systemic adverse effect profiles that appear to be more favorable than those found with traditional therapies, including timolol maleate, These new drugs offer alternatives to the ophthalmologist that also may portend advantages in patient management for both the ophthalmologist and the primary care physician.…”
Section: New Agents With Potentially Reduced Systemic Effectsmentioning
confidence: 99%